Left Pulmonary Artery Thrombosis in a Neonate with Left Lung Hypoplasia. (12th December 2012) - van Schendel, Matthias P.; Visser, Douwe H.; Rammeloo, Lukas A. J.; Hazekamp, Mark G.; Hruda, Jaroslav
Abstract : Thrombotic events in neonates may origin from fetal life. A 4-day-old newborn infant with a family history of heterozygous type 1 protein C deficiency was diagnosed with left lung hypoplasia and left pulmonary artery thrombosis. Its source was prenatally closed ductus arteriosus. Surgical removal of the thrombus was performed.